The Role of Co-Curricular Activities in Islamic Higher Education: Engaging Gen-Z with Developmental Theories - Yusnaini; Nuriman; Setiawan (CV Kalimasada Group, 2025)
The 4.0 Era has revolutionized education through the digital transformation of academic systems and curriculum design. This study investigates the role of co-curricular activities in Islamic higher education and their potential to attract and engage Gen-Z. Theories of humanism, recreation, self-development, and rational choice emphasize the importance of integrating values into co-curricular frameworks. The research also highlights the challenges faced by Islamic institutions, including the limited integration of co-curricular activities and alignment with the career-oriented priorities of Gen-Z.A qualitative approach was employed through document analysis, observation, and in-depth, unstructured interviews to confirm and elaborate on the study's focus. The findings point to the need for co-curricular models that integrate Islamic values, fostering intellectual, social, and spiritual growth while simultaneously enhancing enrolment appeal.